Soil properties, condition and soil losses for south and east Brazilian forest areas - Avanzi, Junior Cesar (2009)
Eucalyptus cultivation has increased in all Brazilian regions. In order to recommend good management practices it is necessary to understand differences in soil properties where eucalyptus is planted. In addition, aggregate stability analyses have proved to be a useful tool to measure soil effects caused by changes in management practices. Besides, the evaluation of soil erosion is an important tool for planning of conservationist management actions allowing appropriate changes on land-use and implementation of sustainable management strategies in the long-term. Thus, the objectives of this study were: i) to determine the main soil properties for different soil classes, and assess the relationship between aggregate stability and changes in soils under eucalyptus plantation, and ii) to predict the potential annual soil loss using the Universal Soil Loss Equation (USLE) coupled in a Geographical Information System (GIS). We studied representative soils within three eucalyptus cultivated regions. In the Espírito Santo state the soils selected were classified as dystrocohesive Yellow Argisol - PA1 (Hapludult), moderately rocky Yellow Argisol - PA2 (Hapludult), and dystrophic Haplic Plinthosol - FX (Phinthaquox). In the Rio Doce Valley, center-east region of Minas Gerais state, the samples were collected in dystrophic Red-Yellow Latosol - LVA (Haplustox) and dystrophic Red Latosol - LV (Haplustox). In the south region of Brazil the area encompasses eutrophic Red Argisol - PVe (Rhodudalf), dystrophic Red-Yellow Argisol - PVA (Hapludult), and dystrophic Haplic Cambisol - CXbd (Dystrudept). Physical, chemical, and mineralogical analyses were performed for the A horizon to characterize the predominant soil profiles. Aggregate stability was measured using the high-energy moisture characteristic (HEMC) technique. Aggregate stability ratio was greater than 50% for all soils. This fact shows for highly weathered soils with large amount of 1:1 clay minerals, that the aggregate stability index was high. In the Espírito Santo we performed the USLE model in order to evaluate soil erosion. All the USLE factors were generated in a distributed approach using GIS framework. Results showed that the average soil loss was 6.2 t ha-1 yr-1. Relative to soil loss tolerance, 86% of the area presented erosion rate smaller than the tolerable value.